Topological and Kinematic Singularities for a Class of Parallel Mechanisms - Nir Shvalb (Mathematical Problems in Engineering, 2009)
We study singularities for a parallel mechanism with a planar moving platform in ℝ𝑑(𝑑=2,3), with joints which are universal, spherical (spatial case), or rotational (planar case). For such mechanisms, we give a necessary condition for a topological singularity to occur, and describe the corresponding kinematic singularity. An example is provided.